Evolução da periodontite experimental em ratos na ausência e presença de hipertensão arterial renovascular - Silva, Lídia Maria Rosa da (2007)
Periodontal disease is a chronic and multifatorial inflammatory disease, that results from a unbalance between the host and the microorganisms of dental biofilm and can lead to tooth loss. Although there are evidences that periodontal disease may influence the general health and the suceptibility to determinated systemic diseases, there are few investigations regarding the relationships between periodontitis and arterial hypertension. Therefore, the goal of this study was to evaluate histological changes induced by renovascular hypertension in rats with periodontal disease. Male Wistar rats (5 week-old, 150-170 g) were separated in two groups: Hypertensive (n=6) and SHAM (n=5). The animals were anesthetized, submitted to laparotomy and only the hypertensive group received a silver clip in the left renal artery (2K1C). Fourteen days after this procedure, the animals were submitted to experimental periodontitis induction through the subgengival ligature at first left inferior molar. The non-ligated contralateral molar was considered as control situation. Once again, fourteen days after the periodontitis induction, the MAP (109±1,4mmHg SHAM vs 178±5mmHg hypertensive) and HR (351±4bpm SHAM vs 370±12bpm hypertensive) hemodynamic measurements were performed in the conscious animals. The animals were sacrificied and the jaw was removed to histological processing. The parameters used to evaluate the periodontitis were: PMNs, the number of blood vessels and alveolar bone loss in the ligated and control molar at distal interproximal region. The results showed that there were a significant raise in PNMs and number of blood vessels at the periodontitis side when compared to control side in SHAM animals (2,2±0,3 vs. 14,6±2,2 and 4,6±0,8 vs. 13,1±1,7 respectively) and hypertensive animals (2,3±0,3 vs. 15±0,9 and 4,5±0,84 vs. 13,1±1,8 respectively). Although there are significant changes between the ligated and non ligated molar in each group, there were no differences in bone loss between the ligated molar of SHAM (0,74±0,07mm) and hypertensive (0,87±0,10mm) animals. Based on these data, we can conclude that in rats, the renovascular hypertension did not agravatted the periodontal disease.